Prioritising the best use of biomass resources - Slade,R; Bauen,A; Gross,R (2010)
Using biomass to provide energy services is one of the most versatile options for increasing the proportion of renewable energy in the existing system. This report reviews metrics used to compare alternative bio-energy pathways and identifies limitations inherent in the way that they are calculated and interpreted. It also looks at how companies and investors approach strategic decisions in the bio-energy area. Bio-energy pathways have has physical and economic attributes that can be measured or modelled. These include: the capital cost, operating cost, emissions to air, land and water. Conceptually, comparing alternative pathways is as simple as selecting the attributes and metrics you consider to be most important and ranking the alternative pathways accordingly. At an abstract level there is good agreement about which features of bio-energy pathways are desirable, but there is little agreement about which performance metrics best capture all the relevant information about a bio-energy pathway. Between studies there is also a great deal of variation and this impedes comparison.Common metrics describe energetic performance, economic performance, environmental performance (emissions, land and water use), and social and ecological performance. Compound metrics may be used to integrate multiple attributes but their highly aggregate nature may make them difficult to interpret.Insights that may be drawn from the analysis include: •The diversity of bio-energy feedstocks and conversion technologies means that there is unlikely to be a one-size-fits-all best use of biomass. •In seeking to develop a strategic approach to biomass use, none of the commonly used metrics capture all pertinent information. •Not all energy services are equally valuable. Some bio-energy applications – e.g. second generation biofuels – may be strategically important even if at current prices the cost-per-tonne-of-carbon-saved appears unattractive. The option value of